Myeloablative Chemotherapy with Autologous Stem Cell Transplant for Desmoplastic Small Round Cell Tumor. (7th April 2015) - Forlenza, Christopher J.; Kushner, Brian H.; Kernan, Nancy; Boulad, Farid; Magnan, Heather; Wexler, Leonard; Wolden, Suzanne L.; LaQuaglia, Michael P.; Modak, Shakeel
Abstract : Desmoplastic small round cell tumor (DSRCT), a rare, aggressive neoplasm, has a poor prognosis. In this prospective study, we evaluated the role of myeloablative chemotherapy, followed by autologous stem cell transplant in improving survival in DSRCT. After high-dose induction chemotherapy and surgery, 19 patients with chemoresponsive DSRCT underwent autologous stem cell transplant. Myeloablative chemotherapy consisted of carboplatin (400–700 mg/m 2 /day for 3 days) + thiotepa (300 mg/m 2 /day for 3 days) ± topotecan (2 mg/m 2 /day for 5 days). All patients were engrafted and there was no treatment-related mortality. Seventeen patients received radiotherapy to sites of prior or residual disease at a median of 12 weeks after transplant. Five-year event-free and overall survival were 11 ± 7% and 16 ± 8%, respectively. Two patients survive disease-free 16 and 19 years after transplant (both in complete remission before transplant). 14 patients had progression and died of disease at a median of 18 months following autologous transplant. These data do not justify the use of myeloablative chemotherapy with carboplatin plus thiotepa in patients with DSRCT. Alternative therapies should be considered for this aggressive neoplasm.